2017
DOI: 10.1007/s10072-017-3218-9
|View full text |Cite
|
Sign up to set email alerts
|

When aphasia is due to aphasic status epilepticus: a diagnostic challenge

Abstract: Aphasic status epilepticus is an uncommon entity that should be included in the differential diagnosis of persistent and sudden language disorders. In our study, we describe seven patients admitted with clinical and electroencephalographic diagnosis of aphasic status, who were studied with both neuroimaging and electroencephalogram. The mean age was 65.9 years (range of 39-89). Three of the patients had previously been diagnosed of epilepsy. The aphasia was global in six patients. In one case, we found foci of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
13
0
2
Order By: Relevance
“…In non-lesional cases, metabolic disturbances, such as nonketotic hyperglycemia (NKH) and aggravated uremia, or drugs, such as cefepime, are reportedly the cause of ASE. [4][5][6]13 There are some reports of cases with combined factors, that is, epileptogenic lesions along with metabolic disturbances. 10,[13][14][15] Metabolic disturbances may act as acute triggering factors for status epilepticus, lowering the seizure threshold in the epileptogenic area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-lesional cases, metabolic disturbances, such as nonketotic hyperglycemia (NKH) and aggravated uremia, or drugs, such as cefepime, are reportedly the cause of ASE. [4][5][6]13 There are some reports of cases with combined factors, that is, epileptogenic lesions along with metabolic disturbances. 10,[13][14][15] Metabolic disturbances may act as acute triggering factors for status epilepticus, lowering the seizure threshold in the epileptogenic area.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 ASE can arise from various neurological or metabolic disorders. [3][4][5][6] It should be differentiated from prolonged postictal aphasia or organic brain disorders, such as stroke. ASE is usually treatable with antiepileptic drugs, but diagnostic delays may cause irreversible neuronal damage.…”
Section: Introductionmentioning
confidence: 99%
“…We had to keep in mind that the development of ictal speech and language dysfunction, as well as eye deviation, could first suggest an acute vascular condition. However, the presence of fluctuating aphasia and additional symptoms suggestive of an epileptic etiology and the fact that the eye deviation is contralateral to the likely affected hemisphere should lead us to suspect the presence of epileptic activity. Furthermore, due to the more widespread use of multiparameter computed tomography of the brain to evaluate acute stroke, reports have emerged describing hyperperfusion in cases that actually have an epileptic origin .…”
Section: Discussionmentioning
confidence: 99%
“…In those contexts, routine EEG were not always conclusive for SE (Flügel et al, 2015) even though itctal EEG patterns have been reported (Patil and Oware, 2012). LPDs have been sometimes described but they have never been marked as ictal pattern even though, in some cases, a clear electro-clinical correlation was described with patient’s good clinical response to the anti-seizure therapy (Quintas et al, 2018). In the largest clinical records (Ericson et al, 2011) nine patients affected by aphasic status epilepticus have been described of whom LPDs were reported in five.…”
Section: Discussionmentioning
confidence: 99%